A novel motion control approach for tethered wheeled mobile robot on extreme terrain - Xiaotao Wang; Xingyu Wang; Jiayou Zhang (International Journal of Advanced Robotic Systems)
Some of the most valuable science targets for future exploration mission located at the extreme terrains of the planetary surfaces are currently inaccessible to the conventional rovers. The tethered mobile robot with one end fixed to the mother robot or an anchor point has the ability to rappel down steep slopes and traverse rocky terrain, and is a reasonable solution to the above missions. Since the model of the tethered mobile robot can be formulated as a cascade of kinematics and dynamics, a novel backstepping motion control approach is proposed in this paper, in which the kinematic and dynamic controllers are designed independently in a recursive way. In the proposed approach, the optimal distribution of the tether tension and the torque to drive the left and right wheels of the tethered robot is obtained based on the minimization of the system power consumption when the robot traveling on the extreme terrains. In addition, a nonlinear disturbance observer is integrated into the dynamic controller to estimate the disturbance from the rugged terrains. Simulations are performed to verify the effectiveness of the proposed algorithm.